(untitled) (Journal of Partial Differential Equations, 2004)
" The author discusses the asymptotic behavior of the radial minimizer of the p-Ginzburg-Landau functional with a weight in the case p > n 2265 2. The location of the zeros and the uniqueness of the radial minimizer are derived. Moreover, the W^1,p convergence of the radial minimizer of this functional is proved."